Impacts of COVID-19 on fish value chains in India: Descriptive evidence from Andhra Pradesh - Loison, S.A.; Shikuku, Kelvin Mashisia; Mohan, A.B.; Babu, R.; Pounds, A. (WorldFish, 2021)
This study aimed at assessing the impacts of the COVID-19 pandemic on fish value chains in India, between 2019 and 2020 and between 2020 and 2021. The specific objectives were to assess the impacts of COVID-19 pandemic on: 1) access by fish value chain actors to inputs for fish production, processing and marketing; 2) fish production and sales; 3) access to markets by value chain actors including impacts on sales, prices and competition; and 4) the welfare of fish value chain actors.